Victims of the Chilean Miracle : Workers and Neoliberalism in the Pinochet Era, 1973-2002 - Winn, Peter (Book collections on Project MUSE., 2004)
An attempt to gauge the impact of Chile's neoliberal reform policies and of the Chilean "economic miracle" on various groups of workers.